2008
DOI: 10.3390/md6010012
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycetes from Sediments in the Trondheim Fjord, Norway: Diversity and Biological Activity

Abstract: Abstract:The marine environment represents a largely untapped source for isolation of new microorganisms with potential to produce biologically active secondary metabolites. Among such microorganisms, Gram-positive actinomycete bacteria are of special interest, since they are known to produce chemically diverse compounds with a wide range of biological activities. We have set out to isolate and characterize actinomycete bacteria from the sediments in one of the largest Norwegian fjords, the Trondheim fjord, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(104 citation statements)
references
References 19 publications
(15 reference statements)
5
90
3
6
Order By: Relevance
“…This phenomenon has resulted in similar or identical finding of compounds from well-known bacteria even though they were isolated from different environments (Bredholt et al, 2008). The reduction of new metabolites discovered has forced the search into new habitats.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This phenomenon has resulted in similar or identical finding of compounds from well-known bacteria even though they were isolated from different environments (Bredholt et al, 2008). The reduction of new metabolites discovered has forced the search into new habitats.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, more global findings have shown that novel bacteria from various extreme or poorly explored environments are capable of producing valuable sources of new bioactive metabolites and compounds (Bredholt et al, 2008;Rojas et al, 2009). Therefore, it is important to determine the taxonomic relationships and metabolic diversity of bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also serve as alternative sources of biologically active substances (Behal, 2003) especially in combating infectious diseases which today are leading health problems with high morbidity and mortality in the developing countries (Black et al, 1982). Several reports are available on antibacterial and antifungal activity of marine actinomycetes (Suthindhiran & Kannabiran, 2009;Bredholt et al, 2008) but relatively few studies are available for Gordonia species. Gordonia tearrae is one of 27 Gordonia species of marine actinomycetes (Arenskotter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Marine sediments have proven a profi table habitat for the isolation of high numbers of Micromonosporaceae (Bredholt et al, 2008;Maldonado et al, 2008;Prieto-Davó et al, 2008). Our isolate, Micromonospora strain DB620, originated from the German Wadden Sea, a unique ecosystem characterized by large areas of tidal fl ats.…”
Section: Introductionmentioning
confidence: 99%